PAX5 alterations in B-cell acute lymphoblastic leukemia - Jia, Zhilian; Gu, Zhaohui (Frontiers in Oncology, 2022)
PAX5, a master regulator of B-lymphoid development and maintenance, is one of the most common targets of genetic alterations in B-cell acute lymphoblastic leukemia (B-ALL). PAX5 alterations consist of copy number variations (whole gene, partial, or intragenic), translocations, and point mutations, with distinct distribution across B-ALL subtypes. The multifaceted functional impact such as haploinsufficiency and gain-of-function of PAX5 depending on specific variants have been described, thereby the connection between the blockage of B-lymphoid development and the malignant transformation of normal B cells has been established. In this review, we provide the recent advances in understanding the function of PAX5 in orchestrating the development of both normal and malignant B-lymphoid cells over the past decade, with a focus on the PAX5 alterations shown as the initiating or driver events in B-ALL. Recent large-scale genomic analyses of B-ALL have identified multiple novel subtypes driven by various PAX5 genetic lesions, such as the one defined by a distinct gene expression profile and PAX5 P80R mutation, which is an exemplar leukemia entity driven by a missense mutation. Although altered PAX5 is shared as a driver in B-ALL, disparate disease phenotypes and clinical outcomes among the patients indicate further heterogeneity of the underlying mechanisms and disturbed gene regulation networks along the disease development. In-depth mechanistic studies in human B-ALL and animal models have demonstrated high penetrance of PAX5 variants alone or concomitant with other genetic lesions in driving B-cell malignancy, indicating the altered PAX5 and deregulated genes may serve as potential therapeutic targets in certain B-ALL cases.